An Israeli Gynecologic Oncology Group study of statin use and endometrial cancer prognosis. Issue 1 (10th October 2019) - Segev, Yakir; Gemer, Ofer; Helpman, Limor; Hag‐Yahia, Nasreen; Eitan, Ram; Raban, Oded; Vaknin, Zvi; Ben‐Arie, Alon; Amit, Amnon; Levy, Tally; Namazov, Ahmed; Voldarsky, Michael; et al.
Abstract: Objective: To assess whether statin use by endometrial cancer patients was associated with a survival advantage. Methods: A retrospective chart review study, by the Israeli Gynecologic Oncology Group, of consecutive endometrial cancer patients who underwent surgery in one of 11 medical centers between 2002 and 2014. Clinical and pathological reports, and measures of survival were compared between statin users and nonusers. Kaplan‐Meier and Cox proportional hazard models were used to assess the effect of using statins on survival measures. Results: Over a mean follow‐up period of 6.2 years (range, 1–12 years) for 2017 endometrial cancer patients with complete data, 663 (32.8%) used statins prior to diagnosis and 1354 (67.1%) did not. No statistically significant differences between the groups were observed for most demographic and clinical characteristics. There was no difference between statin users and nonusers in 5‐year recurrence‐free survival (82% vs 83%; P =0.508), disease‐specific survival (86% vs 84%; P =0.549), or overall survival (77% vs 75%; P =0.901). Conclusions: In this large cohort of patients with endometrial cancer, no significant associations were found between use of statins and endometrial cancer survival. Abstract : In a large cohort of endometrial cancer patients, no significant associations were found between statin use and endometrial cancer survival.